Polarization splitting directional coupler using tilted subwavelength gratings - Luque-González, José Manuel; Herrero-Bermello, Alaine; Ortega-Moñux, Alejandro; Sánchez-Rodriguez, Marina; Velasco, Aitor V.; Schmid, Jens; Cheben, Pavel; Molina-Fernández, Íñigo; Halir, Robert (Optica Publishing Group, 2020)
On-chip polarization splitters are key elements for coherent optical communication systems and polarization diversity circuits. These devices are often implemented with directional couplers that are symmetric for one polarization and strongly asymmetric for the other polarization. To achieve this asymmetry, highly dissimilar waveguides are used in each coupler arm, often requiring additional material layers or etch steps. Here we demonstrate polarization splitting with a directional coupler composed of two fully etched subwavelength waveguides, differing only in the tilt angle of the silicon segments. Our device exhibits deep-UV compatible feature sizes, is 14 µm long, and covers a 72 nm bandwidth with insertion losses below 1 dB and an extinction ratio in excess of 15 dB.
Keywords: Fotones -- Polarización; Fotónica; Photonics